O premeni avstenita pri ohlajanju zvarov jekla Niomol 490 K - Vodopivec, Franc (Materiali in tehnologije, 2004)
On the basis of disponible empirical data an explanation for the higher transition temperature of the brittle-to-ductile fracture is proposed for the heat-affected zone of welds of steel Niomol 490 K. The comparison with a more alloyed steel shows that the transition temperature is increased probably because of the transformation of coarse-grained austenite to lower bainite.
Keywords: konstrukcijska jekla; zvari; mikrostruktura; žilavost; Charpyjev prelom